Annual Cluster Conference "Spatialities": Keynote - Tendayi Sithole (Conference Spatilities 2023, 2023)
As part of the Cluster's international conference on "Spatialities" Tendayi Sithole held a keynote lecture titled: "Azania: Extended Notes on Black Radical Thought - in Dialogue with Bruce Janz (UC Florida)". Tendayi Sithole is Professor in the Department of Political Sciences, University of South Africa. He is also a Senior Research Associate at the Institue for Pan-African Thought and Conversation, University of Johannesburg. Sithole's scholarly books are "Refiguring in Black" (Cambridge, Polity Press, 2023), "The Letter in Black Radical Thought" (Lanham, MD: Lexington Books, 2023), "Mabogo P. More: Philosophical Anthropology in Azania" (New York: Rowman and Littlefield International, 2022), "The Black Register" (Cambridge: Polity Press, 2020), and "Steve Biko: Decolonial Meditations of Black Consciousness (Lanham, MD: Lexington Books, 2016). His book "Black X: Liberatory Thought in Azania" is forthcoming with Wits University Press in 2024. Currently, Sithole is conducting research for a biography provisionally titled "Vinny da Vinci: A Portrait". Bruce Janz is Professor in the Department of Philosophy, co-director of the Center for Humanities and Digital Research, and core faculty in the Texts and Technology program, all at the University of Central Florida. He teaches and writes on African philosophy, cultural philosophy, contemporary European philosophy, digital humanities, and questions of place and space across many disciplines. He has taught in Canada, Kenya, South Africa, and the US. His most recent book is "African Philosophy and Enactivist Cognition: The Space of Thoght" (Bloomsbury, 2023).